2021
DOI: 10.1021/acs.est.1c04608
|View full text |Cite
|
Sign up to set email alerts
|

High Sample Throughput LED Reactor for Facile Characterization of the Quantum Yield Spectrum of Photochemically Produced Reactive Intermediates

Abstract: Photochemically produced reactive intermediates (PPRIs) by natural photosensitizers such as chromophoric dissolved organic matter (CDOM) play numerous key roles in aquatic biogeochemical processes. PPRI productions rely on both the intensity and the spectrum of incident sunlight. While the impacts of sunlight intensity on PPRI productions are well-studied, there remains insufficient understanding of the spectrum-dependence of PPRI productions. Here we designed a high sample throughput reactor equipped with mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…We note that the tidal ROS production efficiency is dependent on hydrological conditions, microbial activity, and soil properties. In the meantime, the incident sunlight intensity may profoundly vary depending on numerous factors (e.g., cloud cover, atmospheric gases, and particles), which can affect photochemical ROS productions . Therefore, the relative importance of tidal and photochemical ROS productions in coastal biogeochemical processes may vary depending on environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that the tidal ROS production efficiency is dependent on hydrological conditions, microbial activity, and soil properties. In the meantime, the incident sunlight intensity may profoundly vary depending on numerous factors (e.g., cloud cover, atmospheric gases, and particles), which can affect photochemical ROS productions . Therefore, the relative importance of tidal and photochemical ROS productions in coastal biogeochemical processes may vary depending on environmental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Dipotassium terephthalate (TPA) was applied as a chemical probe to quantitatively detect • OH production. 30 An excessive amount of TPA probe (1 mM) was added into the reduced coastal soils, and • OH production was assessed by measuring the formation of hydroxyterephthalate (hTPA) through • OHmediated hydroxylation of TPA. Adsorption control shows minor adsorption of hTPA (<10%) on soils (Figure S3).…”
Section: Qualification Of Ros By In Situ Electron Paramagnetic Resona...mentioning
confidence: 99%
“…Prior to irradiation, all DOM concentrations were diluted to 5 mg C L –1 in air-saturated ultrapure water and the solutions were adjusted to pH 7 ± 0.2 by adding 10 mM phosphoric acid and dipotassium hydrogen phosphate. 2,4,6-trimethylphenol (TMP), furfuryl alcohol (FFA), and benzene (BZ) were used as molecular probes for 3 DOM*, 1 O 2 , and • OH, respectively. ,, The initial concentrations of the probes were [TMP] 0 = 100 μM, [FFA] 0 = 10 μM, and [BZ] 0 = 5 mM . Different probe compounds were added separately to measure different reactive intermediates individually.…”
Section: Methodsmentioning
confidence: 99%
“…2,4,6-trimethylphenol (TMP), furfuryl alcohol (FFA), and benzene (BZ) were used as molecular probes for 3 DOM*, 1 O 2 , and • OH, respectively. 18,37,38 The initial concentrations of the probes were [TMP] 0 = 100 μM, 39 [FFA] 0 = 10 μM, 40 and [BZ] 0 = 5 mM. 18 Different probe compounds were added separately to measure different reactive intermediates individually.…”
Section: High-resolution Mass Spectrometry (Hrms)mentioning
confidence: 99%
“…Most interestingly, UV-LEDs provide versatility in emitting light at any designated wavelength . It has been reported that the excitation wavelength significantly impacted the photoreactivity of DOM. For example, an approximately linear decrease of 1 O 2 quantum yield with a longer excitation wavelength in the range of 300–560 nm was observed for DOM irradiated with pulsed laser light . The quantum yields of RS by lake DOM were also found to decrease with irradiation wavelength in the order of UVB > UVA > blue using mercury lamps .…”
Section: Introductionmentioning
confidence: 98%